2013
DOI: 10.1371/journal.pone.0077978
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Genetic Structure between Deep and Shallow Populations of the Southern Rock Lobster, Jasus edwardsii in Tasmania, Australia

Abstract: The southern rock lobster, Jasus edwardsii, shows clear phenotypic differences between shallow water (red coloured) and deeper water (pale coloured) individuals. Translocations of individuals from deeper water to shallower waters are currently being trialled as a management strategy to facilitate a phenotypic change from lower value pale colouration, common in deeper waters, to the higher value red colouration found in shallow waters. Although panmixia across the J. edwardsii range has been long assumed, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…The significant interaction between site and puerulus year (AMOVA neutral SNPs, Table ) found in the present study and the significantly different pairwise F ST values found herein further support the existence of chaotic genetic patchiness. In the case of J. edwardsii , while examination of the adult populations generally concludes panmixia within Australia (Morgan et al., ; Thomas & Bell, ; Villacorta‐Rath et al., ), our analysis including cohorts of pueruli over time and space blurs this conclusion. Recently settled individuals (stage 1–2 pueruli) analysed in the present study exhibited a nonsignificant global level of genetic differentiation ( F ST = −0.0042), suggesting that there is gene flow between South Australia and Tasmania.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The significant interaction between site and puerulus year (AMOVA neutral SNPs, Table ) found in the present study and the significantly different pairwise F ST values found herein further support the existence of chaotic genetic patchiness. In the case of J. edwardsii , while examination of the adult populations generally concludes panmixia within Australia (Morgan et al., ; Thomas & Bell, ; Villacorta‐Rath et al., ), our analysis including cohorts of pueruli over time and space blurs this conclusion. Recently settled individuals (stage 1–2 pueruli) analysed in the present study exhibited a nonsignificant global level of genetic differentiation ( F ST = −0.0042), suggesting that there is gene flow between South Australia and Tasmania.…”
Section: Discussionmentioning
confidence: 69%
“…It occupies a wide geographic range, approximately between 110–180°E and 30–50°S, and subpopulations are exposed to different temperature regimes along this latitudinal gradient (Hinojosa et al., ). Studies assessing population structure of J. edwardsii have distinguished large‐scale neutral and adaptive differences between populations in Australia and New Zealand (Morgan, Green, Murphy, & Strugnell, ; Thomas & Bell, ; Villacorta‐Rath et al., ). Although the sampling design of those studies did not allow structure in adult populations to be distinguished at a regional level, larval transport simulations suggest that there is genetic exchange between populations in Australia (Bruce, Griffin, & Bradford, ).…”
Section: Introductionmentioning
confidence: 99%
“…Key results from field trials were that slow-growing lobsters that were moved to inshore areas: (a) changed colour within a year (Chandrapavan et al, 2009a); (b) increased their growth rates to that of the new site (Chandrapavan et al, 2010); (c) survived in their new location ); (d) increased egg production ; (e) improved their condition and body chemistry (Chandrapavan et al, 2009b(Chandrapavan et al, , 2011a); (f) changed body morphology to a higher valued shape (Chandrapavan et al, 2011b); and (g) stayed at the release site (Green et al, 2013b). This research also demonstrated that these changes were phenotypic, not genetic (Morgan et al, 2013).…”
Section: Introductionmentioning
confidence: 57%
“…These differences are phenotypic rather than genetic (Morgan et al, 2013), with lobsters from deep-water regions in the south west of Tasmania tending to grow slowly in high density populations, while lobsters from shallow-water or northern areas grow far more rapidly (Gardner et al, 2006;Punt and Kennedy, 1997). Translocation involves capturing slow growing lobsters that are below the minimum legal size and moving these lobsters to regions where their growth improves and they develop more valuable market traits (Chandrapavan et al, 2010(Chandrapavan et al, , 2011a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation